Analisis Potensi, Efektivitas Dan Laju Pertumbuhan Penerimaan Retribusi Parkir Pada Dinas Perhubungan Kabupaten Malang - Angguliyah Rizqi Amaliyah; Doni Teguh Wibowo (Universitas PGRI Madiun, 2021)
This study aims to determine the acceptance of parking fees at the Malang district transportation service by analyzing the potential, effectiveness and growth rate during the period 2016 to 2019. The research design used uses a quantitative approach. The sample used is the parking fee receipt data for the period 2016 to 2019 at the Malang Regency Transportation Service. Secondary data that had been collected were analyzed by means of potential, effectiveness and growth rate. From the results of research that has been done, the results of the potential for receiving parking fees are in prime and developing categories, have very potential results with increased growth rates (positive). The results of the effectiveness of receiving parking fees are in the very effective category. This category defines and shows that the performance of the Malang Regency Government at the Department of Transportation in the parking fees section is capable of managing and managing its retribution receipts for the four periods. The results for four years show the growth rate of parking fees with a positive growth coefficient.